The Oversight Function of the Regional House of Representatives on Regional Development: An Empirical Study in Makassar City - Basdir; Bachtiar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2025)
This study aims to analyze the implementation of the supervisory function of the Makassar City Regional House of Representatives (DPRD) in regional development and to identify the supporting and inhibiting factors influencing its effectiveness. The research employed a quantitative descriptive approach with a census method involving all 50 members of the Makassar City DPRD as respondents. Data were collected through questionnaires, interviews, observation, and documentation, and analyzed using descriptive statistical techniques. The findings indicate that the supervisory function of the DPRD is conducted through the use of institutional rights such as interpellation, inquiry, and the right to express opinions. The effectiveness of supervision is supported by cooperation between the executive and legislative branches, which strengthens the checks and balances mechanism. However, limitations remain in internal control mechanisms and systematic preventive supervision. The study highlights that strengthening institutional capacity and transparency is crucial to improving legislative oversight in regional development governance.